Gastronomi ve Mutfak Sanatinda Baharatlar ile Tibbi ve Aromatik Bitkilerin Kullanimi (The Usage of Spices and Medicinal and Aromatic Plants in Gastronomy and Culinary Arts) - Cilginoglu, Hakki; Aliu, Dorian; Aliu, Armando (Elsevier BV, 2018)
Turkish Abstract: Bu calismanin amaci, gastronomi ve mutfak sanatinda baharatlar ile tibbi ve aromatik bitkilerin kullanim alanlarini incelemektir. Gastronominin bilim ile yemek arasindaki bagi dusunuldugunde, monotonlasan insan hayatinin renklendirilmesi mutfak sanatinda baharatlar ile tibbi ve aromatik bitkilerin yenilikci kullanimlari sayesinde gerceklesebilmektedir. Bu baglamda, farkli ulkelerde ve bolgelerde yetisen bazi tibbi ve aromatik bitkilerin mutfaklarda duyusal cekiciligi artirici sekilde gastronomi ile tesvik edilmektedir. Dunya capinda binlerce bitkinin farkli amaclarla kullanildigi goz onune alindiginda, gastronomi ve mutfak sanatinda kullanilan tibbi ve aromatik bitkilerin incelenmesi bu alana katki bakimindan onemli oldugu degerlendirilmistir. Bu calisma kapsaminda sinirli sayida tibbi ve aromatik bitki spesifik ozellikleri ile ornek teskil etmesi bakimindan literaturden secilmistir. Soz konusu bitkilerin seciminde; gastronomi ve mutfak sanati icerisinde kullanimi, yenilikci ve surdurulebilir anlayisi yansitma ozellikleri arastirmanin sinirliligi cercevesinde dikkate alinmistir. English Abstract: The aim of this study is to examine the use of spices and medicinal and aromatic plants in gastronomy and culinary arts. Considering the nexus amongst gastronomy and food and science, the colouring of monotonised human life is likelihood to be attained through the innovative usage of spices and medicinal and aromatic plants in the culinary arts. In this context, some medicinal and aromatic plants that are cultivated in various countries and regions are encouraged by gastronomy, which enhances sensory attractiveness in culinary arts. Taking into account the fact that thousands of plants are used for different purposes worldwide, the examination of medicinal and aromatic plants used in gastronomy and culinary arts is evaluated to be important in terms of contributing to this field. Within the scope of this study, a limited number of medicinal and aromatic plant-specific attributes are selected from the literature to be exemplary. In the selection of these plants; their usages in gastronomy and culinary arts, and their ability to reflect innovative and sustainable insights were taken into consideration in frame of the investigation’s limitation.
Keywords: 3. Good health